The Future of the Conservation Province of West Papua in Supporting the Production of Basic Foodstuffs and Poverty Eradication - Obadja A. Fenetiruma; Yunita Palinggi (Jurnal Penelitian Pendidikan IPA, 2025)
The West Papua Provincial Government in 2018 declared West Papua as a Province of Sustainable Development, which was reinforced by the enactment of Regional Regulation No. 10 of 2019.  In its development, West Papua Province was then divided into two provinces, namely West Papua and West Papua South. With the enactment of the second revision of the Special Autonomy Law No. 2 of 2021, the threat of regional division has grown, including the shrinking of productive agricultural land in food-producing areas.  The objectives of this study are to (1) examine the development of provincial conservation policies in West Papua; (2) explore the agenda for regional division accompanied by commitments to sustainable development in West Papua Province; and (3) analyze the production capacity of staple foods in West Papua Province.  This research is a case study in which West Papua Province was deliberately selected. A descriptive method with a desk study approach was used as the data analysis method. The results of the study concluded that (1) the current West Papua Conservation Province policy is not running as it should; (2) the policy of forming new autonomous regions (DOB) has caused each cultural entity to focus on expanding itself and neglecting the sustainable development commitments initiated since 2015; and (3) the production of staple food commodities, particularly rice, in West Papua has experienced a drastic decline over the past five years, threatening local food security.  West Papua is projected to face a rice deficit of 23.27 tons by 2025.